2004
DOI: 10.1017/s0252921100002281
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Short Period Double-Degenerate Binaries

Abstract: Abstract. We review the current observational status of the ROSAT sources RX J1914.4+2456 and RX J0806.3+1527, and the evidence that these are ultra-short period (< 10 min) binary systems. We argue that an Intermediate Polar interpretation can be ruled out, that they are indeed compact binaries with a degenerate secondary, and that the period seen in the X-ray and optical is the orbital period. A white dwarf primary is preferred, but a neutron star cannot be excluded. We examine the capability of the three cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…The unipolar-inductor model avoids the above difficulties of the accretion models. Although the model is generally consistent with existing observations (see Cropper et al 2004), there are some concerns regarding whether or not it is applicable to RX J1914+24 and RX J0806+15, which are presumably compact white-dwarf pairs (e.g. Barros et al 2005Barros et al , 2007Laine, Lin & Dong 2008;Wood 2009).…”
Section: K Wusupporting
confidence: 76%
See 1 more Smart Citation
“…The unipolar-inductor model avoids the above difficulties of the accretion models. Although the model is generally consistent with existing observations (see Cropper et al 2004), there are some concerns regarding whether or not it is applicable to RX J1914+24 and RX J0806+15, which are presumably compact white-dwarf pairs (e.g. Barros et al 2005Barros et al , 2007Laine, Lin & Dong 2008;Wood 2009).…”
Section: K Wusupporting
confidence: 76%
“…The unipolar-inductor model, however, suggested that the emission of X-rays is caused by ohmic dissipation of electric currents in the white-dwarf atmosphere. An assessment of the models can be found in Cropper et al (2004). In the face-on IP model, a moderately magnetized white dwarf is accreting material from a mainsequence donor star.…”
Section: Candidate Unipolar-inductor Ultra-compact Double Degeneratesmentioning
confidence: 99%
“…The properties of RX J0806.3+1527 and its "twin" RX J1914.4+2456 (V407 Vul), which displays a 569-s (9.5-min) modulation and overall similar X-ray and optical properties, are interpreted in the framework of a double-degenerate binary that hosts two interacting white dwarfs (WDs), where the observed pulsation is due to orbital motion (see Cropper et al 2004; Solheim 2010 for reviews). Roelofs et al (2010) showed in RX J0806.3+1527 a clear modulation of He emission lines in both radial velocity and amplitude on the 5.4-min period (see also Mason et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The observational constraints for the systems HM Cnc and V407 Vul were discussed in detail in Paper I (also see Cropper et al 2004). Briefly, the systems are characterized by ‘on/off’ X‐ray light curves that trail the optical light curves by roughly 0.2 in phase (Barros et al 2007, and references therein), no hard X‐rays are detected, the observed periods are decreasing with time at a rate consistent with gravitational radiation angular momentum loss (Strohmayer 2003, 2004; Ramsay, Cropper & Hakala 2006), and flickering is minimal or absent (Barros et al 2007).…”
Section: Introductionmentioning
confidence: 99%